Como a alfabetização científica se desenvolve no contexto da educação básica: um olhar sobre a prática docente - Stranghetti, Natalia (Universidade Federal de São Carlos, 2025)
This study aimed to analyze the presence and development of Scientific Literacy (SC) in Basic Education, highlighting its relevance as an essential tool for understanding and applying scientific knowledge in everyday life and in the modern world. To this end, Chemistry classes were monitored in two state schools, seeking to identify the presence of SC in basic education. In addition, the teachers of these classes were interviewed, allowing a qualitative analysis based on the principles of Bardin's Content Analysis. Initially, SC indicators observed during classes were collected, while categories were created for essential aspects that did not appear, but are fundamental for the development of SC in education. In order to deepen the investigation, interviews were conducted with other teachers from the state network to understand their perceptions about SC. The research also included the analysis of legislation and documents guiding education in Brazil, such as the National Common Curricular Base (BNCC) and the Law of Guidelines and Bases of National Education, in order to verify how SC is addressed in curricula and pedagogical guidelines. The results indicated that CA is present in Basic Education, but there is a vast potential that has not yet been explored, since several essential parameters were not identified in the observed teaching practice. The study suggests that CA could be significantly more stimulated if there were greater awareness and guidance among education professionals about its importance. In addition to the lack of specific knowledge, it was found that the limited time allocated to the study of teaching tools and methods compromises the development of pedagogical practices that facilitate the learning and understanding of scientific content.
How scientific literacy develops in the context of basic education: a look into teaching practices
Keywords: Alfabetização científica; Alfabetização tecnológica; Indicadores de alfabetização científica; Prática pedagógica; Scientific literacy; Technological literacy; Scientific literacy indicators; Pedagogical practice; CIENCIAS EXATAS E DA TERRA::QUIMICA